Kontrol Nutrisi Tanaman Hidroponik Berbasis Monitoring Internet of Things - Rouhillah, Rouhillah; Salfikar, Inzar; Ichan, Maulidi (Elektron : Jurnal Ilmiah, 2022)
Hydroponics is a way of farming that does not use soil, but only uses water that contains nutrients. The growth of hydroponic plants can be influenced by various factors, one of which is a lack of water nutrition in hydroponic plants. Therefore, this study aims to create a system that functions to control water nutrition, as well as the availability of sufficient water in hydroponic reservoirs. This control process uses NodeMCU esp8266 and processes sensor data and then sends it to firebase which will be displayed to Android with Internet of Thing (IoT) technology. If the nutritional condition being monitored is reduced, this nutrition control device will receive input from the sensor to add nutrients automatically. The addition of nutrients uses an on-off control system, when the TDS sensor reads the water nutrients are reduced the nutrient pump will be on until it reaches the initial nutrient setpoint, then the nutrient pump will be off. The result of reading sensor data obtains the percentage error for the Total Dissolve Solid (TDS) sensor with a comparison of TDS meter of 5.746%.